Scitovsky, behavioural economics, and beyond - Maurizio Pugno (Economics: The Open-Access, Open-Assessment E-Journal, 2014)
Scitovsky is known as a forerunner of behavioural economics simply because he drew heavily on psychology and claimed that people's choices may be "joyless" (Scitovsky, The joyless economy, 1976). However, a careful reformulation of his analysis shows that he anticipated a number of insights (also with respect to Kahneman's "two-systems of thought" which suggest new lines of inquiry from an original and different perspective. These insights of Scitovsky regard the following aspects: Uncertainty as a condition where the outcomes of choosing a particular option (novelty) is partially unknown; the case of individual "consumption skill" (inclusive of emotions) that finds this uncertainty desirable when it is challenging; the case of increasing such skill so as to change preferences and make choices more efficient; the case of failing to increase such skill so as to make addictive harmful products an alternative and more tempting option.
Keywords: B31; D03; D11; 330; Scitovsky; behavioural economics; novelty; consumption skill; strong uncertainty; harmful addiction